Perancangan Aplikasi Terapi Musik untuk Penderita Anxiety Menggunakan Pendekatan Human Centered Design (HCD), Persona, dan Minimum Viable Product (MVP) - Dyah Utami, Kartika; Kusuma, Wahyu Teja; Anshori, Mochammad (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
Anxiety represents a prevalent mental disorder among individuals in their productive years, significantly affecting quality of life and psychological well-being. The present study aimed to design a music therapy application as a non-pharmacological intervention for alleviating anxiety symptoms. Nineteen respondents aged 20–24 years with diagnosed anxiety disorders in the Malang region participated in the study. The application was developed using Human-Centered Design (HCD) approaches, persona methodology, and Minimum Viable Product (MVP) principles. Therapeutic music categories included guided meditation tracks, nature sounds, and 432Hz frequency compositions, all validated by a hypnotherapy specialist. Prototype evaluation was conducted through user needs mapping (persona goals) and expert validation procedures. Results demonstrate that the prototype successfully addressed three core indicators: PG.1 (access to therapeutic music catalog), PG.2 (music search functionality), and PG.3 (playback interface design). These features were engineered to deliver accessible relaxation experiences for independent use. The research establishes that integrating HCD, persona, and MVP methodologies can generate solutions grounded in authentic user requirements. Study limitations include the restricted sample size and absence of long-term effectiveness assessment. Future research should investigate emotion-based music personalization features to enhance therapeutic outcomes.